Delivery by caesarean section and offspring adiposity and cardio‐metabolic health at ages 6.5, 11.5 and 16 years: results from the PROBIT cohort in Belarus. Issue 9 (3rd March 2021) - Rifas‐Shiman, Sheryl L; Huh, Susanna Y; Martin, Richard M; Kramer, Michael; Patel, Rita; Bogdanovich, Natalia; Vilchuck, Konstanin; Thompson, Jennifer; Oken, Emily
Summary: Background: Caesarean delivery has been associated with later adiposity, perhaps via early programming or perhaps because of residual confounding by maternal or birth characteristics. Objectives: Examine associations of caesarean delivery with adiposity and cardio‐metabolic biomarkers. Methods: Observational analysis of 15 069 children in the PROBIT cohort in Belarus. We examined measures of child anthropometry and blood pressure at 6.5, 11.5 and 16 years and fasting blood (11.5 years). Results: Caesarean‐delivered children were slightly heavier at 6.5 (mean BMI 15.8 vs. 15.6 kg/m 2 ), 11.5 (18.4 vs. 18.2) and 16 years (21.5 vs. 21.3). After adjustment for prenatal characteristics including maternal third trimester BMI, however, we observed no association of caesarean versus vaginal delivery with child BMI (β 0.05 kg/m 2 ; 95%CI: −0.03, 0.14), sum of skinfolds (0.14 mm; −0.13, 0.42), waist circumference (−0.07 cm; −0.23, 0.10), obesity (OR 0.99; 0.76, 1.29), or systolic (−0.20 mmHg; −0.70, 0.30) or diastolic (−0.17 mmHg, −0.60, 0.26) blood pressure at 6.5 years; results were similar at 11.5 and 16 years. At 11.5 years, we observed a modest association of caesarean delivery with fasting insulin (0.33 mU/L; 0.00, 0.65). Conclusions: Caesarean delivery had little or no association with adiposity or related cardio‐metabolic biomarkers in childhood. Adjustment for maternal BMI attenuated all outcome effect estimates.